Rapid detection, characterization, and enumeration of foodborne pathogens - Hoorfar, J. (ASM Press, 2011)
Growing public concern over the safety of our food supply has fueled the research and development of new methods to detect foodborne pathogens as quickly and as early as possible. This reader-friendly reference examines the latest proven rapid foodborne pathogen detection methods currently used. Organized by food commodities, this unique book enables readers to choose the most effective and efficient method, assemble the necessary resources, and implement the method seamlessly, avoiding common pitfalls. Rapid Detection, Characterization, and Enumeration of Foodborne Pathogens is organized into seven sections. The first two sections review the latest laboratory technologies designed to accelerate test results, and explain the issues that labs need to consider in order to effectively implement rapid detection methods. The next four sections are organized according to commodity and food production lines, enabling readers to easily find the best pathogen detection methods for their needs. For each food line, the book sets forth the rapid methods that can detect important target pathogens. The final section looks to the future, detailing research needs and emerging areas of rapid detection of foodborne pathogens. More than 85 experts from worldwide research centers provide guidelines for faster, user-friendly, and cost-effective foodborne pathogen detection. Their advice is based not only on a thorough review of the current literature, but also their own first-hand laboratory experience. As a result, readers can confidently turn to this book to minimize the risk of pathogen-contaminated foods reaching consumers.